The celebrity chef phenomenon: a (reflective) commentary. Issue 2 (11th February 2019) - Zopiatis, Anastasios; Melanthiou, Yioula
Abstract : Purpose: This paper aims to explore the nature of the celebrity chef phenomenon and its impact on the contemporary hospitality industry, to both enrich current knowledge on the topic, as well as inform future research endeavors. Design/methodology/approach: The study was based on a narrative literature review of secondary data sources, namely, academic literature and industry-related articles, and video data collected from popular video-hosting websites. Findings: Despite the vast popularity of celebrity chefs, the phenomenon remains underexplored, with limited coverage given to it by hospitality-related literature. Prior investigations primarily focused on celebrity chefs' commercial influence and power of advocacy, with little reference to their impact on the next generation of culinary professionals and on the sustainability of the profession. Research limitations/implications: This commentary has numerous theoretical and practical implications for industry stakeholders who wish to explore this phenomenon beyond the limited confinements of its commercial impact. In particular, the study explores the nature of the phenomenon, where television, social media and the celebrity status of chefs influence both the values and norms surrounding the profession, and individuals' vocational choices. That said, findings suggest that additional research is required on this topic. Originality/value: The exploration of celebrity chefs as a topic has so far been limited and has leaned toward one dimension in hospitality literature, despite its interesting scope. This critical overview provides conceptual clarity on issues such as the phenomenon's commercial and vocational impact and highlights areas of concern and opportunity. Moreover, the study sets a clear pathway for further research.